638 Plasma proteome analysis in patients with immune checkpoint inhibitors related arthritis and pneumonitis. (9th November 2020) - Abdel-Wahab, Noha; Diab, Adi; Katayama, Hiroyuki; Kim, Sang; Hanash, Samir; Suarez-Almazor, Maria
Abstract : Background: Immune checkpoint inhibitors (ICIs) have resulted in unprecedented advances in the treatment of cancer. By disinhibiting the immune system, they enhance anti-tumor immunity, but provoke off-target inflammatory and immune-related adverse events (irAEs) which can seriously impact morbidity and mortality. The exact immunobiology of irAEs is not completely understood, but may involve specific immune pathways. To date, there is no validated biomarker test to predict the development of irAEs in patients treated with ICIs. Methods: To identify possible biomarkers of irAEs, we performed in-depth proteomic profiling of blood samples obtained from cancer patients receiving ICIs. The plasmas were processed with Hu-14 immuno-depletion column (Agilent Technologies) and the samples were labeled with TMT (Thermo Scientific). The proteins were next pre-fractionated with HPLC, trypsin digested and analyzed by nanoAQUITY LC coupled Synapt G2-Si ion-mobility mass spectrometry (WATERS). Results: A total of 12 patients were enrolled in the study; all were receiving anti-programmed cell death-1 (PD-1) agents. Cancer types included melanoma (n=9), renal cell carcinoma (n=2), and non-small cell lung cancer (n=1). Eight patients had irAEs with active toxicity symptoms at blood draw (4 with pneumonitis-irAE and 4 with arthritis-irAE); 6 of those patients were receiving corticosteroids (ranging from 5 to 60 mg/d), and 1 was receiving tocilizumab (an anti-IL-6 receptor antibody). Four patients who completed a minimum of one year of anti-PD1 treatments without irAEs were enrolled as control group. Median time from ICI initiation until blood draw was 16 months (range, 4–31) among patients with irAEs and 23 months (range, 17–28) among controls.We identified 925 protein gene products from 2.5 million mass spectra that can cover 107 dynamic range of plasma proteins. Among them, 19 proteins showed statistically significant differences between patients with and without irAEs (P<0.05) (figure 1). Nine proteins including CFB, CLEC3B, ITIH4, HPX, RARRES2, TF, OAF, MYL12A, and MYL12B were significantly upregulated in patients with irAEs; MYL12A and MYL12B are known to be elevated in airway inflammation of lung tissues. While, 10 other proteins including APOC4, AVPR2, B9D1, DPEP2, JCHAIN, LINC00238, PLG, RAB40C, TCF4, and ZFP30 were significantly downregulated in patients with irAEs (figure 2). Conclusions: In-depth plasma proteome analysis identified possible biomarkers of adverse events modulated by ICI treatment. We plan a prospective validation cohort study of melanoma patients initiating treatment with ICIs to further evaluate the potential clinical utility of the identified biomarkers and their association with immune toxicity, and tumor response to ICI therapy. Ethics Approval: The study was approved by The Institutional Review Board at The University of Texas MD Anderson Cancer Center, approval number PA16-0928 Consent: Written informed consent was obtained from all patients who agreed to participate in the study